Basic income on the agenda : policy objectives and political chances - Veen, Robert van der; Groot, L. F. M. (Lucas Franciscus Michaël), 1962- (Amsterdam : Amsterdam University Press ; London : Eurospan, 2000)
A inquiry into the pros and cons of an unconditional basic income.
In search of the double-edged sword / Paul de Beer -- Basic income and its cognates: partial basic income versus earned income tax credit and reductions of Social Security contributions as alternative ways of addressing the 'new social question' / Philippe van Parijs, Laurence Jacquet and Claudio Caesar Salinas -- Activation and the burden of working: on instrument choice by a responsibility-sensitive egalitarian government / Frank Vandenbroucke and Tom Van Puyenbroeck -- Arguing for a negative income tax in Germany / Joachim Mitschke -- Hush money or emancipation fee? A gender analysis of basic income / Ingrid Robeyns -- Prospects for basic income in an age of inactivity? / Anton Hemerijk -- Basic income and social Europe / Fritz W. Scharpf -- Basic income at the heart of social Europe? Reply to Fritz Scharpf / Philippe Van Parijs -- European basic income or the race to the bottom: why politicians might come to think the unthinkable / Steve Quilley.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Minimum wage -- Europe; Income maintenance programs; Basic income; Basic income -- Government policy -- Europe; Income maintenance programs -- Government policy -- Europe; Sécurité du revenu; Sécurité du revenu -- Politique gouvernementale -- Europe; Revenu annuel garanti; Revenu annuel garanti -- Politique gouvernementale -- Europe; Salaires minimums -- Europe; Society and culture: general; SOCIAL SCIENCE -- Poverty & Homelessness; POLITICAL SCIENCE -- Comparative Politics; Income maintenance programs; Basic income -- Government policy; Basic income; Minimum wage; Europe; Mindestlohn; Europa; Basisinkomen; Overheidsbeleid; Amsterdam <2000>; Sociology: work and labour; Labour / income economics; Welfare economics; Electronic books